(untitled) (Journal of the College of Basic Education, 2022)
In this paper, analytical solution of the fractional heat equation has been presented. The algorithm for the analytical solution for this equation is based on modified Adomian’s decomposition method. The fractional derivative is described in Caputo’s sense. The analytical method has been applied to solve a practical example and the results have been compared with exact solution